The Influence of Service Quality, Facilities, and Price on Customer Satisfaction at Estetica Belle Salon - DEWI, Ni Komang Indah Sari; GANAWATI, Nengah; SELAMET, I Ketut (PT Batara Swastika Harati, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are the largest group of economic actors in Indonesia's economy and have proven to be a safety valve for the national economy during crises. Besides being the sector with the greatest contribution to national development, MSMEs also create significant job opportunities for the domestic workforce, thus helping to reduce unemployment. This study aims to determine how service quality, facilities, and price influence customer satisfaction at Estetica Belle Salon, both simultaneously and partially. The sampling method used in this research is Slovin's formula, resulting in 100 respondents. The data analysis technique employed in this study is multiple linear regression analysis, including instrument testing and classical assumption tests beforehand. This research data uses quantitative data by collecting data questionnaires. This research shows that facility service quality and price have a positive and significant effect on customer satisfaction simultaneously. This shows that Quality has a positive and significant effect on Customer Satisfaction. Facilities have a positive and significant effect on customer satisfaction. Price has a positive and significant effect on customer satisfaction.